Identifikasi Perkembangan Lahan Terbangun di Kota Tanjung Pinang Tahun 2004-2024 - Dea Rizky Saputri; Arie Afriadi; Nefriwati Hilmi; Aria Bagiasa Chidmahdjati; Hoki Apriyenson (Pusat riset dan Inovasi Nasional, 2025)
The development of built-up land in Tanjungpinang City has demonstrated rapid spatial dynamics, in line with the increasing intensity of urban activities since its designation as the capital of Riau Islands Province in 2002. This study aims to analyze the changes in built-up land in Tanjungpinang City over the period 2003 to 2023 and to identify the key factors driving this transformation. The research employed spatial analysis based on Geographic Information Systems (GIS), utilizing satellite imagery maps from the years 2003, 2013, and 2023. The findings indicate that built-up land expanded from 1,133.91 hectares (8%) in 2003 to 3,848.67 hectares (26%) in 2023, with the predominant direction of expansion occurring toward the eastern and southern parts of the city. The primary factors contributing to this growth include population increase, the development of new activity centers such as Pulau Dompak, and the construction of major infrastructure, notably the development of DI Panjaitan streets. These results suggest a growing tendency toward urban sprawl in the physical development of Tanjungpinang City, thus requiring adaptive and sustainable spatial planning strategies.